Bloom's Taxonomy and Reading Comprehension in English Teaching: Evaluating Teacher's Questioning - Franklin Untailawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This study investigates how high school English teachers in different locations (SMA Negeri 3 in Aru Island Regency and SMA Negeri 4 in central Maluku Regency) utilize Bloom’s taxonomy in their questions to improve students’ reading comprehension. Using qualitative methods such as observation, interviews, and documentation, the researcher reveals various question types employed by these teachers, ranging from literal to appreciation questions. Analyzing the questions through Bloom’s taxonomy, the study finds that while teachers cover cognitive levels from understanding to evaluation, questions related to analysis and evaluation are relatively scarce. This suggests a potential oversight in fostering critical thinking skills in reading comprehension instruction. Despite this, the study concludes that the learning process leads to notable improvements in students’ reading comprehension at these schools.